The Relations Between Eastern and Western Civilizations in the Middle Ages - Andrijauskas, Antanas (Acta Orientalia Vilnensia, 2001)
The author of the article deals with different aspects of the relations between Eastern and Western civilizations in the Middle Ages. Close attention is paid to the study interchange between Byzantine, Western Christian, Islamic, Indian and Chinese civilizations. Surely there must have been something to sustain them for over 1000 years and make particularly popular nowadays. They are essentially two interlocked aspects of an integral world, traditional models of the world - universal formative principles at the core of cultural codes and intelligent ways of the East and West. The latter should replace traditional ones which seem too simplistic in their characteristic overestimation of the East and West dimension of world cultures.Comparative methodology accepts the relativism of contemporary studies of civilizations and admits that the traditional principles and methods of thinking yielded by Western civilization cannot be regarded as universal and encompassing all of human nature. Therefore, it supplements the traditional demand for impartiality with a new methodic stipulation that the cultural and social perspective of the student of the relations between Eastern and Western civilizations in the Middle Ages should not influence the strategy of the comparative analysis.